Age estimation of belugas, Delphinapterus leucas, using fatty acid composition: A promising method. Issue 3 (2nd April 2015) - Marcoux, Marianne; Lesage, Véronique; Thiemann, Gregory W.; Iverson, Sara J.; Ferguson, Steven H.
Abstract Data about age‐specific survival and mortality rate, as well as life history parameters are essential for studying population demography. However, noninvasive methods for ageing free‐ranging marine mammals are generally lacking. Recently, a few studies have highlighted the potential of using fatty acid (FA) composition in blubber biopsy samples to estimate age in some cetaceans. Here, we explore the opportunity of using this technique to estimate the age of free‐ranging belugas from three different populations. Belugas (Delphinapterus leucas) were sampled postmortem for blubber FA analysis and aged by counting the number of growth layer groups in teeth dentine. We found significant positive and negative relationships between some FAs and age. These relationships were stronger with outer blubber layer samples, the layer most accessible via biopsy, than with inner or middle layer samples, a pattern that is consistent with observed turnover rates and biological function across the blubber depth. The FA 12:0, 14:1n‐7, and 14:1n‐9 were promising correlates of age in belugas, allowing estimation of age with a precision of ±7–10 yr. Further work is required to determine the mechanisms underlying changes in FA composition with age and whether these mechanisms are stable through time and across populations.